Implementasi Strategi Diferesiasi dan Adaptasi dalam Pengembangan Daya Saing Bisnis Co-Working Space (Studi Kasus pada Jofter Group) - Budi Wahyono; Arif Hidayat; Sri Mulyani (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The development of the service industry in the era of globalization and digitalization is characterized by increasingly fierce competition and dynamic changes in customer needs. This phenomenon also occurs in the co-working space industry, which is required to not only provide workspace but also offer added value through flexible, innovative, and user-experience-oriented services. Jofter Group, as one of the co-working space service providers, faces the challenge of high competition, requiring the right strategy to maintain and improve its business competitiveness. This study aims to describe and analyze the implementation of differentiation and adaptation strategies in developing the competitiveness of the co-working space business at Jofter Group, including the internal and external factors that influence it, the impact of the strategy on competitiveness and business sustainability, as well as the challenges and strategic efforts undertaken. This study uses a qualitative method with a case study approach. Data collection techniques were carried out through in-depth interviews, observation, and documentation, while data analysis was conducted descriptively-qualitatively. The results show that Jofter Group's differentiation strategy is realized through integrated services, package flexibility, and the integration of business support facilities that can increase customer satisfaction and loyalty. The adaptation strategy is reflected in the company's ability to adjust services, utilize digital technology, and respond quickly to changing market needs. The implementation of these two strategies has a positive impact on competitiveness, brand image, and business sustainability. The conclusion of this study confirms that the synergy between differentiation and adaptation strategies is a key factor in enhancing the competitiveness of co-working space businesses. The originality of this research lies in the in-depth disclosure of the actual practices of differentiation and adaptation strategies in the context of the co-working space industry through a qualitative case study approach.